Cross-contamination and infection control in intraoral digital imaging: a comprehensive review - GÜMRÜ TARÇIN, BİRSAY; TARÇIN, BİLGE (SPRINGER, 2021)
Dental health care workers are subjected to various infectious disease agents that are present in patients' saliva and blood which make infection control and universal prevention methods indispensable to the dental practice given that some of these diseases cause loss of work and time for dental staff and patients; some of them cause serious morbidity; and some of them currently have a poor prognosis and no effective treatments. Although dental radiographic procedures are not invasive, and there are no incidents such as injuries caused by dental instruments, they are a potential infection source because of contamination with saliva and blood, and comprehensive infection control procedures also apply to the radiology clinic. In addition, contact with a large number of patients in dental schools and clinics in a short period of time, and the fact that radiographic procedures are performed in the same environment as other dental procedures in dental offices increase the significance of infection control in dental radiology. Major advances in computer technology have enabled digital imaging systems to develop rapidly and to become common in dental practice as an alternative to conventional film-based imaging. The use of digital sensors in dental radiology introduced unique infection control challenges and required the revision and modification of existing infection control techniques. In this review, studies concerning the risk of cross-contamination and challenges of infection control with digital image sensors are comprehensively reviewed and infection control protocols that should be followed in intraoral digital imaging using both direct and indirect systems are thoroughly examined.
Keywords: Cross-infection; Dentistry; Digital radiology; Imaging receptor; Infection control; MICROBIOLOGIC CONTAMINATION; PHOSPHOR PLATE; RADIOGRAPHY